Detection of Staphylococcus aureus enterotoxins genes in food collected from local markets at Baghdad city - Areej Zuhair Azeez; Yasameen Ibrahim Farhan; Ahmed Ibrahim Jessim; Saad Sabah Fakhry; Maha muhamed khudiar; Ali Abdulqader Adulbaqi; Lubna Ayad Ismail (World Journal of Experimental Biosciences, 2016)
This study represents the record of assessment for the level of contamination by Staphylococcus aureus of certain categories of animal source food and characterization of enterotoxigenic strains. That was done dependent on Polymerase Chain Reaction (PCR) for identification genes coding for the production of toxin by Staphylococcus (SE). On basis of that information were compared the results obtained by PCR approximately the presence in the tested strains of genes encoding the enterotoxin. Number of coagulase-positive staphylococci was performed. At the end of incubation period of 24 h at 37 °C, the typical colonies were sub-cultured on triptycase soy broth, biochemical identification was subsequently completed in micro-method with the API Staph system. S. aureus were isolated from foods and confirmed by PCR with the identification of genus, species and toxins gene. From 350 tested food samples, (48.9%) were contaminated with S. aureus. From all tested samples, the percentage of contamination of fresh meat was 30.2 % from total number of samples, also including fresh meat preparations like sausages (the percentage of contamination was 18.7%. The fresh meat contamination levels were varied from 5 CFU/gm to 720 CFU/gm. It was found 19 toxigenic strains were isolated from meat products. They have proven to be carriers of genes coding to SE, in other hand there were 5 toxigenic strains isolated from pastry, ground beef and shell fish they were tested as a positive for SE. Use of innovative techniques for identification of genes encoding the production of enterotoxins, in addition to classic method of detection, allows identify gene carriers strains they could produce, in suitable conditions, toxins also different from those traditionally.
Keywords: Bacteria, Enterotoxins, Food safety, PCR, Staphylococcus aureus, Toxigenic.